2010
DOI: 10.1007/s11999-009-1103-4
|View full text |Cite
|
Sign up to set email alerts
|

Healed Cuff Repairs Impart Normal Shoulder Scores in Those 65 Years of Age and Older

Abstract: Background It is unclear whether repaired rotator cuffs heal in older patients and whether the function in those shoulders compares with those of similarly aged patients with untreated tears. Questions/Purpose We questioned whether, in patients 65 years of age and older, shoulders with rotator cuff repairs that remained intact would have Simple Shoulder Test (SST) scores and Constant scores similar to those of untreated individuals with intact rotator cuffs. Methods We retrospectively reviewed 39 patients (42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The SST is frequently used to evaluate ADL in cases of shoulder joint disorders because it is easy to perform but also sensitively reflects shoulder dysfunction attributed to shoulder joint disorders. It does not bias the examiner into a particular direction, and it has excellent reproducibility [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The SST is frequently used to evaluate ADL in cases of shoulder joint disorders because it is easy to perform but also sensitively reflects shoulder dysfunction attributed to shoulder joint disorders. It does not bias the examiner into a particular direction, and it has excellent reproducibility [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…81 Healing rate can be affected more by the technique used for the repair than by the approach used. 84 Nonhealed patient had lower values of Constant scores, with age significantly related to the failed repair. 82 Wall, in a systematic review of level I and II studies on the outcomes of single versus double row in RC repair, found no differences in terms of clinical results.…”
Section: Clinical Resultsmentioning
confidence: 87%
“…8,15,50,51 Arthroscopic debridement and partial repair can be considered to reduce symptoms and increase function, with deterioration of the results over time. 80,84,85 Surgical techniques have evolved to reduce morbidity and increase both clinical and anatomical results, but the results of the most recent studies are similar to the ones presented in the 1990s, with clinical results outcomes not directly matching imaging results. 80,84,85 Surgical techniques have evolved to reduce morbidity and increase both clinical and anatomical results, but the results of the most recent studies are similar to the ones presented in the 1990s, with clinical results outcomes not directly matching imaging results.…”
Section: Discussionmentioning
confidence: 99%
“…There are concerns about cuff healing in this particular population group, 3 and significantly lower healing rates in patients of 65 years who had undergone arthroscopic cuff repairs have been reported 17 . Open rotator cuff repairs, however, have been reported to have higher healing rates, 18 and patients with healed cuffs also imparted similar SST and CSS to 200 patients with untreated intact rotator cuffs. Functional outcome does not necessarily correlate with the anatomical outcome, 19 and large proportion of patients who are found to have proven defect at follow‐up still report improved comfort, satisfaction and improved CSS compared with preoperatively 13,20,21 …”
Section: Discussionmentioning
confidence: 99%